A Novel N-Tetrasaccharide in Patients with Congenital Disorders of Glycosylation, Including Asparagine-Linked Glycosylation Protein 1, Phosphomannomutase 2, and Mannose Phosphate Isomerase Deficiencies. (6th January 2020) - Zhang, Wenyue; James, Philip M; Ng, Bobby G; Li, Xueli; Xia, Baoyun; Rong, Jiang; Asif, Ghazia; Raymond, Kimiyo; Jones, Melanie A; Hegde, Madhuri; Ju, Tongzhong; Cummings, Richard D; et al.
Abstract: BACKGROUND: Primary deficiencies in mannosylation of N-glycans are seen in a majority of patients with congenital disorders of glycosylation (CDG). We report the discovery of a series of novel N-glycans in sera, plasma, and cultured skin fibroblasts from patients with CDG having deficient mannosylation. METHOD: We used LC-MS/MS and MALDI-TOF-MS analysis to identify and quantify a novel N-linked tetrasaccharide linked to the protein core, an N-tetrasaccharide (Neu5Acα2, 6Galβ1, 4-GlcNAcβ1, 4GlcNAc) in plasma, serum glycoproteins, and a fibroblast lysate from patients with CDG caused by ALG1 [ALG1 (asparagine-linked glycosylation protein 1), chitobiosyldiphosphodolichol β-mannosyltransferase], PMM2 (phosphomannomutase 2), and MPI (mannose phosphate isomerase). RESULTS: Glycoproteins in sera, plasma, or cell lysate from ALG1-CDG, PMM2-CDG, and MPI-CDG patients had substantially more N-tetrasaccharide than unaffected controls. We observed a >80% decline in relative concentrations of the N-tetrasaccharide in MPI-CDG plasma after mannose therapy in 1 patient and in ALG1-CDG fibroblasts in vitro supplemented with mannose. CONCLUSIONS: This novel N-tetrasaccharide could serve as a diagnostic marker of ALG1-, PMM2-, or MPI-CDG for screening of these 3 common CDG subtypes that comprise >70% of CDG type I patients. Its quantification by LC-MS/MS may be useful for monitoring therapeutic efficacy of mannose. The discovery of these small N-glycans also indicates the presence of an alternative pathway in N-glycosylation not recognized previously, but its biological significance remains to be studied.